2009
DOI: 10.1016/j.brainres.2009.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant neuroprotection against ethanol-induced apoptosis in HN2-5 cells

Abstract: Earlier studies from this and other laboratories show that ethanol induces apoptotic death of fetal and neonatal neurons. One mechanism that underlies these effects is the ethanol-associated reduction in the phosphatidylinositol 3′ kinase pro-survival pathway. Another mechanism involves the oxidative stress caused by the ethanol-associated increase in reactive oxygen species (ROS).In the present study, we used the murine HN2-5 hippocampal-derived cell line to investigate the effects of ethanol on ROS levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…Firstly, some neurotransmission systems have demonstrated therapeutic potential in FASD (Choong and Shen 2003;Ryan et al 2008;Shen and Choong 2006;Thomas et al 2004Thomas et al , 2007Xu and Shen 2001), and PPAR-alpha was able to modulate those systems (De La Monte et al 2006;Farioli-Vecchioli et al 2001;Galan-Rodriguez et al 2009;Melis et al 2008). Secondly, there are reports of the value of anti-oxidant treatments in countering the harmful effects of in utero exposure to alcohol (Ramachandran et al 2003;Rathinam et al 2006;Sheth et al 2009), and PPAR-alpha constitutes a pharmacological target that is likely to modulate several downstream physiopathological pathways involved in neuronal survival, including those that protect the cell from oxidative stress (Bordet et al 2006;Girnun et al 2002).…”
Section: Discussionmentioning
confidence: 94%
“…Firstly, some neurotransmission systems have demonstrated therapeutic potential in FASD (Choong and Shen 2003;Ryan et al 2008;Shen and Choong 2006;Thomas et al 2004Thomas et al , 2007Xu and Shen 2001), and PPAR-alpha was able to modulate those systems (De La Monte et al 2006;Farioli-Vecchioli et al 2001;Galan-Rodriguez et al 2009;Melis et al 2008). Secondly, there are reports of the value of anti-oxidant treatments in countering the harmful effects of in utero exposure to alcohol (Ramachandran et al 2003;Rathinam et al 2006;Sheth et al 2009), and PPAR-alpha constitutes a pharmacological target that is likely to modulate several downstream physiopathological pathways involved in neuronal survival, including those that protect the cell from oxidative stress (Bordet et al 2006;Girnun et al 2002).…”
Section: Discussionmentioning
confidence: 94%
“…Nopparat et al (2010) have demonstrated, in the SK-N-SH dopaminergic cell line, a novel role of melatonin in protecting cells from autophagic cell death triggered by the Bcl-2/Beclin 1 pathway, by inhibiting the activation of the JNK1 (cJun amino-terminal kinase), Bcl-2 upstream pathway. Melatonin increased Bcl-2 and augmented expression of XIAP in ethanol-treated HN2-5 (mouse hippocampal neuron-derived) cells (Shetha et al 2009). Our results also demonstrated an increase in the mRNA expression of AIF in the dentate gyrus of old and ovariectomized rats, and this could suggest that this brain area was following a different apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It attenuates apoptosis and oxidative stress in neurons and mesenchymal stem cells by upregulating the antiapoptotic protein bcl-2 [83,84]. It also alters the cell death processes in response to age-related oxidative stress and apoptosis in the brain of senescenceaccelerated mice [85]. It inhibits the ethanol-induced increased ROS level and increases the bcl-2 expression in murine HN2-5 hippocampus-derived cell line [86].…”
Section: Melatonin As Antiapoptotic Moleculementioning
confidence: 98%